P067 Medical student education in sleep and its disorders: still meagre 20 years on. (19th November 2019) - Romiszewski, Stephanie; May, Felix; Homan, Jane; Norris, Ben; Miller, Michelle; Zeman, Adam
Abstract : Introduction: Stores' questionnaires survey in 1998 found that UK medical students received a median of 20 minutes education about sleep. We asked whether this situation has improved. Methods: A cross sectional survey of 34 medical degree courses in the UK adapted from Stores '1998 questionnaire including time spent on sleep teaching medicine, sub-topics covered, and forms of assessment. Results: 25 (74%) UK medical schools responded to our survey. The time spent devoted to sleep medicine during undergraduate training was median 1.5 hours, mode <1 hour, and mean 3.2 hours (standard deviation = 2.6, figure 1 ). Only two schools had a sleep syllabus or dedicated compulsory module (8%, figure 2 ). When asked whether sufficient time is allotted to sleep and its disorders, 50% said yes, 38% said no and 13% were unsure. Free text comments made by our respondents had recurring themes: sleep medicine is typically subsumed into teaching by other specialities, with the result that course directors are uncertain about the details of provision; obstructive sleep apnoea is often identified as the key or only relevant sleep disorder, knowledge of sleep disorders is regarded as optional, and there is inertia about the prospect of change. However, a substantial minority of respondents are enthusiastic about making improvements to the sleep education they currently provide. Discussion: Sleep medicine remains a neglected topic despite agreement on the importance of sleep in general health. Obstacles to change are similar to those noted by Stores 20 over 20 years ago, including the views that 'sleep is not a core topic' or the 'curriculum is already too crowded'. Given that doctors are often the first point of contact for the public, we recommend that medical schools should establish and implement a sleep medicine curriculum. We suggest a simple syllabus, available on request. References: Greenstone M, Hack M. Obstructive sleep apnoea. BMJ Br. Med. J 2014;348 . Ferrie JE, Kumari M, Salo P, Singh-Manoux A, Kivimäki M. Sleep epidemiology-A rapidly growing field. Int. J. Epidemiol 2011;40:1431–1437. Bjorvatn B, Grønli J, Pallesen S. Prevalence of different parasomnias in the general population. Sleep Med 2010;11:1031–1034. Hafner M, Stepanek M, Taylor J, Troxel WM, van Stolk C. Why sleep matters—the economic costs of insufficient sleep: a cross-country comparative analysis. Rand health quarterly 2017;6 . NICE. Continuous positive airway airway pressure for the treatment of obstructive sleep apnoea/hypopnoea syndrome. Technology Appraisal Guidance 2008. Zeman A, Zaiwalla Z. Prescribing sodium oxybate for narcolepsy. BMJ 2016;353:i2367. National Institute for Health and Care Excellence. Insomnia. Clinical Knowledge Summaries 2015. Available at: https://cks.nice.org.uk/insomnia. (Accessed: 3rd January 2018) Stores G, Crawford C. Medical student education in sleep and its disorders. J R Coll Physicians L 1998;32:149–153. Rosen RC, Rosekind M, Rosevear C, Cole WE, Dement WC. Physician education in sleep and sleep disorders: A national survey of U.S. medical schools. Sleep 1993;16:249–254. Mindell, J. A. et al. Sleep education in medical school curriculum: A glimpse across countries. Sleep Med 2011;12 :928–931. Dyas JV. et al. Patients' and clinicians' experiences of consultations in primary care for sleep problems and insomnia: A focus group study. Br. J. Gen. Pract 2010;60 :180–200. Nowell LS, Norris JM, White DE, Moules NJ. Thematic Analysis: Striving to Meet the Trustworthiness Criteria. Int. J. Qual. Methods 2017;16 :1–13. Youngren WA, Miller KE, Davis JL. An Assessment of Medical Practitioners' Knowledge of, Experience with, and Treatment Attitudes Towards Sleep Disorders and Nightmares. J. Clin. Psychol. Med. Settings 2019;26 :166–172. Salas RME, et al. Incorporating sleep medicine content into medical school through neuroscience core curricula. Neurology 2018;91 :597–610. Smith AG. A sleep medicine medical school curriculum. Neurology 2018;91 :587–588.